International trade, intellectual property rights and the (un)employment of migrants - Lucas Guichard; Ignat Stepanok (The World Economy, 2023)
We study the effect of trade liberalisation and intellectual property rights (IPR) protection on the unemployment rate of migrants relative to nonmigrants. We build a North–South trade and growth model with a positive steady state rate of migration. We find that bilateral trade liberalisation decreases the relative unemployment rate of migrants when migration is low and increases the relative unemployment rate when the migration rate is high. The results do not rely on assumptions about network effects, the probability to find a job for a migrant is independent of the relative size of the migrant diaspora. IPR protection leads to a higher relative unemployment rate of migrants regardless of the size of migration. We provide suggestive empirical evidence in line with the theoretical predictions on trade liberalisation and IPR protection using data for 20 OECD countries over the period 2000–2014.
Keywords: 330; intellectual property rights; migration; North–South trade; trade liberalisation; unemployment